2003
DOI: 10.1001/archotol.129.12.1322
|View full text |Cite
|
Sign up to set email alerts
|

Significance of c-Myc and Bcl-2 Protein Expression in Nasopharyngeal Carcinoma

Abstract: Expression of Bcl-2 and c-Myc protein seems to be a useful marker to reflect irradiation response and to predict illness condition and patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…Our results concerning BCL2 gene expression are in accordance with two other independent studies, conducted on Turkish and Chinese patients, which revealed the overexpression of BCL2 in 74.3% and 57.0% of patients, respectively. However, no correlation between BCL2 expression and clinical features was shown in these studies [46,47].…”
Section: Discussionmentioning
confidence: 69%
“…Our results concerning BCL2 gene expression are in accordance with two other independent studies, conducted on Turkish and Chinese patients, which revealed the overexpression of BCL2 in 74.3% and 57.0% of patients, respectively. However, no correlation between BCL2 expression and clinical features was shown in these studies [46,47].…”
Section: Discussionmentioning
confidence: 69%
“…However, Bcl-2 is overexpressed in the majority of NPC tumors (61-89%), even in the absence of detectable LMP1 expression, and it is postulated that Bcl-2 may play a critical role in promoting cell survival and mediating resistance to chemotherapeutic agents in NPC. [6][7][8][9][10][11][12] Thus, Bcl-2 represents a rational therapeutic target in NPC.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although a direct link between LMP-1 expression, Bcl-2 upregulation and cell survival in NPC is unclear, the majority of NPC tumors overexpress Bcl-2, even in the absence of LMP-1 expression. [6][7][8][9][10][11][12] Given the antiapoptotic function of Bcl-2 and its role in conferring resistance to chemotherapy, it represents a rational target for modulation using antisense strategies in NPC.…”
Section: Epstein-barr Virus (Ebv) Is Causally Linked To Undifferentiamentioning
confidence: 99%
See 1 more Smart Citation
“…More and more scholars have accepted the theory that tumors originate from CSCs. In addition to the above characteristics, CSCs also express several relatively specific biomarkers, such as CD133 [5], CD44 [6], NaNOG [7], and SOX2 [8], and overexpress anti-apoptotic genes, oncogenes, and other malignant biological markers, including telomerase and its hTERT subunit [9], BcL-2 [10], and survivin [11]. CSCs, tumor-like stem cells, or side population cells have been isolated from a variety of malignant tumors, including NPC [12,13].…”
Section: Introductionmentioning
confidence: 99%